2021
DOI: 10.3748/wjg.v27.i23.3303
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal involvement in paediatric COVID-19 — from pathogenesis to clinical management: A comprehensive review

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), the causative agent of coronavirus disease 2019 (COVID-19), is responsible for the first pandemic of the 21 st century. As found in adults, signs and symptoms related to the disease mainly involve the respiratory tract in the paediatric population. However, a considerable number of children present with gastrointestinal symptoms such as vomiting, abdominal pain, and diarrhea. The purpose of this review is an accurate descripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 70 publications
0
25
0
2
Order By: Relevance
“…The most common symptom reported in patients not requiring hospital admission was fever followed by general symptoms and respiratory symptoms. Gastrointestinal symptoms were more rarely observed, and, differently from what observed in the general population, there was no difference among adults and children in the incidence of gastrointestinal symptoms [ 21 , 22 ]. In our pediatric cohort, we did not identify any case of multisystem inflammatory syndrome in children (MIS-C).…”
Section: Discussionmentioning
confidence: 99%
“…The most common symptom reported in patients not requiring hospital admission was fever followed by general symptoms and respiratory symptoms. Gastrointestinal symptoms were more rarely observed, and, differently from what observed in the general population, there was no difference among adults and children in the incidence of gastrointestinal symptoms [ 21 , 22 ]. In our pediatric cohort, we did not identify any case of multisystem inflammatory syndrome in children (MIS-C).…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring CD patients must be adapted to the pandemic to avoid unnecessary endoscopic examinations and duodenal biopsies. Telemedicine can be a good alternative for educating and monitoring chronic patients, keeping away from the risk of unwarranted interventions and viral transmission [ 95 ].…”
Section: Celiac Disease In Children During Covid Pandemicmentioning
confidence: 99%
“…A second proposed mechanism of GI and hepatobiliary injury involves inflammatory and immune mediators. COVID-19 disease has been associated with markedly increased levels of inflammatory markers and cytokines, including interleukin-1 (IL-1), IL-6, and tumor necrosis factor-alpha (TNF-α), which may lead to an accumulation of immune cells in the GI tract [ 76 ] and induce hepatocellular cholestasis by downregulating hepatobiliary uptake and excretory systems. [ 77 , 78 ] Some authors have suggested that immunosuppression is beneficial in blunting cytokine release, leading to improved outcomes.…”
Section: Mechanisms Of Gastrointestinal and Hepatobiliary Injurymentioning
confidence: 99%